Mechanical feedback mechanisms in a multiscale sliding filament model of lymphatic muscle pumping - Peter Y. Xie; Christopher J. Morris; Christopher D. Bertram; Michael J. Davis; Samira Jamalian; Mohammad Jafarnejad; David C. Zawieja; James E. Moore, Jr (Applications in Engineering Science)
The lymphatic system maintains bodily fluid balance by returning interstitial fluid to the venous system. Flow can occur through a combination of extrinsic pumping, due to forces from surrounding tissues, and intrinsic pumping involving contractions of muscle in the lymphatic vessel walls. Lymph transport is important not only for fluid homeostasis, but also for immune function, as lymph is a carrier for immune cells. Lymphatic muscle cells exhibit both cardiac-like phasic contractions to generate flow and smooth-muscle-like tonic contractions to regulate flow. Lymphatic vessels are sensitive to mechanical stimuli, including flow-induced shear stresses and pressure-induced vessel stretch. These forces modulate biochemical pathways, leading to changes in intracellular calcium that trigger contractile proteins. Employing a multiscale computational model of lymphatic muscle coupled to a lumped-parameter model of lymphatic pumping, we developed and validated a feedback control model of subcellular mechanisms that modulate lymphatic pumping. Following verification that the model reproduced results from axial or transmural pressure difference-controlled experiments, we tested the model's ability to match results from experiments imposing upstream/downstream pressure ramps or a sudden increase in downstream resistance. Inter-lymphangion signaling was necessary to reproduce downstream pressure ramp experiments, but otherwise the model predicted behaviors under these more complex conditions. A better understanding of the mechanobiology of lymphatic contractions can help guide future lymphatic vessel experiments, providing a basis for developing better treatments for lymphatic dysfunction.